Sigmodontinos (Rodentia: Cricetidae) del límite pleistoceno-holoceno en el valle de Tafí (Tucumán, Argentina): taxonomía, tafonomía y significación paleoambiental - Ortiz, Pablo Edmundo (2007)
A fossilsample of sigmodontine rodents from Tafí del Valle, Tucumán, Argentina (26º 51´ 43´´ S, 65º 43´ 06´´ W, 2007 m) was studied. A radiocarbon datation on bone fragments indicates that the sample can be referred to the Pleistocene-Holocene boundary (10.25 - 9.65 cal. ky BP). The sample is dominated by the phyllotines Calomys cf. C. musculinus (Thomas) and Phyllotis sp., followed by Akodon spegazzinii Thomas and Reithrodon auritus (Fischer). At the microscopy the surface of bones and teeth shows evidences of corrosion and digestion suggesting the assemblage was generated by the predatory activity of owls. Most of the species from the assemblage correspond to common elements of high altitude grasslands environments from northwestern Argentina, except for R. auritus. All species are currently sympatric in an area about 1000 meters above the fossiliferous locality, in a colder and drier environment than the study site. These facts allowed to infer drier and colder paleoenvironmental conditions at the deposition time than the current ones during the Pleistocene-Holocene boundary in Tafí del Valle.